Hepatoprotective Essential Oils: A Review - Nour Elhouda Daoudi; Mohamed Bnouham (Korean Pharmacopuncture Institute, 2020)
Objectives: Several toxins and molecules are able to damage the liver, causing the hepato- toxicity. This disorder can be protected naturally, by some essential oils obtained from different plants. In this review we are cited some of these compounds that have been tested by their hepatoprotective effect. Methods: We reviewed 83 articles published between 1981 and 2018 in English via three databases Sciencedirect, Springer and PubMed. So, we have used the keywords: Hepatoprotective effect, liver disease, plants and essential oils. Results: and conclusion: In this work, we classified the plants; contain the essential oils, in alphabetical order as a table containing the scientific, family names, information plants, the experimental assay and the results obtained from the hepatoprotective studies. We have described 27 species belonging to 12 families: Lamiaceae (7 species), Asteraceae (6 species), Umbellifereae (3 species), Apiaceae (3 species) are the main families which enclose the species that was studied. The study also includes the major compounds isolated from some of these essential oils. The most of those compounds belong to terpene class essentially cineol, carvacrol and thymol. Thus, the different essential oils that have been cited in this review were shown that have an antioxidant activity.